汽车变速器传动效率理论建模与实验测试 - 王熙; 秦大同; 胡明辉; 周保华 (Jixie chuandong)
By the analysis of factors that influence on the vehicle transmission efficiency,the theoretical analysis model of transmission efficiency is established.For the specific structure of the transmission shift,the vehicle transmission efficiency of various shifts is calculated and tested.The measured results and theoretical results have good consistency,and the correctness of the theoretical model is verified.It provides the basis for the forecast of vehicle transmission efficiency and optimal matching of vehicle powertrain.